Analysis of Product Collection, Prices and Marketing of Industrial Products at PT Metro Mesin Mendunia Malang - Darmawan, Hanafi Arif; Hidayati, Nur; Jatmiko, Udik (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
The food product processing business in Indonesia is developing very quickly, so competition is increasing. The potential of a company called PT. Metro Machine World, which is located in Malang, shows the industrial business of various quality machines and affordable prices with various consumer needs. The aim of the research is to study and analyze the collection of products produced, the prices offered, and the marketing of industrial machines. The research method is interview studies and discussions with related parties related to the potential of machine products and qualitative analysis. The parameters measured are product collections within 2 years from 2022 to 2024, selling prices, and names of consumers who need industrial machines. The results of the research explain that the most popular marketing products are food processing industrial machines consisting of agricultural, fishery, and livestock processed products. The lowest price is an ice crusher machine worth IDR 1,500.00 and the highest marketing price is IDR 145,000,000 for a beverage machine. The consumers who need it the most are the Islamic University of Malang and PT. Buana Prima Raya and MSMEs. Machine marketing uses social media such as WhatsApp, Instagram, TikTok, and National Online Stores.